Hematidrosis and Hemolacria: a rare case of bloody sweat and tears - Musa, Noraini; Abd Rahman, Mohd Aizuddin; Kamaruzaman, Nor Azam; Osman, Iskandar Firzada (2021)
Hematidrosis is a very mysterious disorder in which healthy skin secretes blood while hemolacria is bloody tears. Scarce case reports mainly occurred in adolescent Asian girls. The majority were caused by psychogenic stress although systemic disease, blood problems, and strenuous physical exertion are possible etiologies. Specific investigation to establish the diagnosis is still a dilemma but a greater challenge in primary care is to identify and manage the stressor in a teenage patient.